Dendritic Cell Response to HIV-1 Is Controlled by Differentiation Programs in the Cells and Strain-Specific Properties of the Virus - Nasi, Aikaterini; Amu, Sylvie; Göthlin, Mårten; Jansson, Marianne; Nagy, Noemi; Chiodi, Francesca; Réthi, Bence (Frontiers in Immunology, 2017)
Dendritic cells (DCs) are potent antigen presenting cells that might play contradictory roles during HIV-1 infection, contributing to anti-viral immunity but also to viral dissemination and immune evasion. Although DCs are characterized by enormous functional diversity, it has not been analyzed how differentially programmed DCs interact with HIV-1. We have previously described the reprogramming of DC development by endogenously produced lactic acid that accumulated in a cell culture density dependent manner and provided a long-lasting anti-inflammatory signal to the cells. By exploiting this mechanism we generated immunostimulatory DCs characterized by the production of TH1 polarizing and inflammatory mediators or, alternatively, suppressed DCs that produce IL-10 upon activation, and we tested the interaction of these DC types with different HIV-1 strains. Cytokine patterns were monitored in HIV-1 exposed DC cultures. Our results showed that DCs receiving suppressive developmental program strongly upregulated their capacity to produce the TH1 polarizing cytokine IL-12 and the inflammatory chemokines CCL2 and CCL7 upon interaction with HIV-1 strains IIIB and SF162. On the contrary, HIV-1 abolished cytokine production in the more inflammatory DC types. Pre-incubation of the cells with the HIV-1 proteins gp120 and Nef could inhibit IL-12 production irrespectively of the tested DC types, whereas MyD88- and TRIF-dependent signals stimulated IL-12 production in the suppressed DC type only. Rewiring of DC cytokines did not require DC infections or ligation of the HIV-1 receptor CD209. A third HIV-1 strain, BaL could not modulate DC cytokines in a similar manner indicating that individual HIV-1 strains can differ in their capacity to influence cytokine production in DCs. Our results demonstrated that HIV-1 could not induce definite and invariable modulatory programs in DCs. Instead, interaction with the virus triggered different responses in different DC types. The outcome of DC-HIV-1 interactions might thus be highly variable, shaped by endogenous features of the cells and diversity of the virus.